Using museum visits to enhance CPD for early years professionals. (2nd May 2023) - Norman, Amanda
Abstract : Senior lecturer at the University of Winchester and early years consultant, Dr Amanda Norman, discusses her project to use museum visits to enhance a community of practice and a sense of belonging between early years practitioners, as part of continuous professional development.